Genetic Assessment of Remnant Sub-Populations of Sterlet (Acipenser ruthenus Linnaeus, 1758) in the Upper Danube - Thomas Friedrich; Dietmar Lieckfeldt; Arne Ludwig (Diversity, 2022)
While the potamodromous sterlet was common in the past throughout the Upper Danube in Germany and Austria, it nearly vanished in the second half of the 20th century. Until recently, only one small and isolated reproductive sub-population is known from the German–Austrian border. However, isolated remnants in another section downstream of Vienna, near the Austrian–Slovakian border, were discovered in 2014. An assessment of the population size is one of the most important prerequisites for conservation management. This study aims to assess the population sizes at both sites, using genetic pedigrees and comparison to mark–recapture data. A total of 193 samples collected from these populations between 2011 and 2021 have been investigated. In addition, 59 samples from captive stocks, 38 wild fish from downstream, and 247 genetic profiles from previous studies were used for comparison. Results show close relationships and intermittent reproduction on one site. Estimated populations based upon genetic pedigree are very small, and are consistent with mark–recapture results. Small population sizes of remnant populations have only limited, sporadic reproduction, as well as continual losses to outmigration support conservation actions for sturgeons in the Upper Danube, including the restoration of functional migration corridors.